Experimental and Theoretical Study of the Stability of the Complex Fisetin–Cu(II) and A Comparative Study of Free Ligand and Complex Interaction with Molecular Singlet Oxygen - Muñoz, Vanesa Alejandra (2020)
In this work, the flavonol fisetin was selected in order to study its reactivity against Cu(II), a metal ion of interest in biological media and industry. The stoichiometry and apparent formation constant of the complex in ethanolic medium at 25°C were evaluated using spectrophotometric techniques. The resulting stoichiometry was a 1:1 ligand:metal complex, and a log K = 5.17 ± 0.12 was determined. Since two possible chelation sites can be proposed for the complex formation, quantum chemistry calculations were performed on these structures. Calculations suggest that the hydroxyl-keto site is more stable for the complex formation than the catechol site. Flavonoids could exert protection against oxidative damage caused by reactive oxygen species, and this biological activity could be affected by chelation with metal ions. This led us to perform a study on the interaction of both, free flavonoid and complex, with reactive oxygen species. Our results showed both compounds quench molecular singlet oxygen photogenerated with visible light, mainly in a physical fashion. In order to analyze a possible protective effect of flavonoid and its complex against oxidative damage in biological environments, the amino acid tryptophan was selected as a model oxidation system. Free flavonoid does not have a marked protective effect, whereas its complex showed a relevant protective effect.